Bibliometric Analysis: Business Innovation Research Trends in the Post-Election Era - Nur Rachman, Saskia Fadilla (Prosiding Seminar Nasional Ilmu Manajemen, Ekonomi, Keuangan dan Bisnis, 2024)
Elections are identified as a driver of social and political change that influences the business climate. The study used bibliometric analysis of 10 scientific articles from 2014 to 2024 to analyze research trends. Findings show variations in the number of publications over time, with a focus on adaptive business strategy, business model innovation, and capital markets integration. Dominant keywords include economy, sentiment, election, government, and policy. The research results provide insight into how post-election changes affect business innovation, providing important implications for business practitioners in responding to these changes.